Bio-efficacy of halosulfuron methyl against Cyperus spp. in maize (Zea mays L.) - Kumar, Anil; Sharma, Neetu; Sharma, Ashu; Mahajan, Amit; Stanzen, Lobzang (Annals of Agricultural Research, 2016)
A field experiment was conducted at research farm, Division of Agronomy SKUAST-Jammu to evaluate the efficacy of halosulfuron-methyl for the control of Cyperus and other weed species in maize. The treatments comprised of two different doses of halosulfuron-methyl post-emergence @ 52.5 & 67.5 g/ha, 2,4-D ethyl ester post-emergence @ 900 ml/ha, atrazine pre-emergence @ 500 g/ha, two hand weeding at 20 and 35 DAS and untreated control. The results revealed that the lowest density and dry weight of Cyperus spp. as well as higher weed control efficiency and grain yield of the maize crop were recorded with post-emergence application of halosulfuron-methyl @ 67.5 g/ha which was closely followed by 2, 4-D ethyl ester @ 900 ml/ha The herbicide doses evaluated in this study did not show any phytotoxicity and residual effect on succeeding wheat crop.